Collaboration ABCGM+ In Developing Tourism Nglanggeran Village Gunung Kidul Regency 2018 - Nurhadiyanti; Zaenuri, Muchammad (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2020)
Nglanggeran Village is one of the tourist villages that is occupied being discussed even abroad. It was succeed in turning the best tourism village at the ASEAN level. Therefore, it is one of the reasons for this research to analyze the collaboration ABCGM+ in developing tourism in Nglanggeran village. This research is a qualitative research with a case study approach which intends to look at the activities carried out in the daily life of the community as well as the interaction process in groups or individuals. The results of the research related to the collaboration ABCGM + in the development of tourism in Nglanggeran village showed that to be sure there was collaboration between 6 (six) stakeholders related. Be that as it may, the key stakeholders who are the driving actors in the development of tourism in Nglanggeran village are the tourism conscious group (Pokdarwis). The synergy that occurs between each stakeholder cannot be separated from the existence of the tourism conscious group (Pokdarwis).